The molecular chaperone calnexin facilitates folding and assembly of class I histocompatibility molecules. - Vassilakos, A (1996)
Calnexin, a membrane protein of the endoplasmic reticulum, is generally thought to function as a molecular chaperone, based on indirect or correlative evidence. To examine calnexin's functions more directly, we reconstituted the assembly of class I histocompatibility molecules in the absence or presence of calnexin in Drosophila melanogaster cells. Calnexin enhanced the assembly of class I heavy chains with beta 2-microglobulin as much as 5-fold. The improved assembly appeared largely due to more efficient folding of heavy chains, as evidenced by increased reactivity with a conformation-sensitive monoclonal antibody and by a reduction in the level of aggregates. Similar findings were obtained in mouse or human cells when the interaction of calnexin with class I heavy chains was prevented by treatment with the oligosaccharide processing inhibitor castanospermine. The ability of calnexin to facilitate castanospermine. The ability of calnexin to facilitate heavy chain folding and to prevent the formation of aggregates provides compelling evidence that calnexin functions as a bona fide molecular chaperone.